Association Between Perioperative Hypoalbuminemia And Anastomotic Leakage In Esophageal Carcinoma Patients Undergoing Esophageal Resection (Journal of Chittagong Medical College Teachers' Association, 2026)
Background: Anastomotic Leakage (AL) is a serious complication after esophagectomy, increasing morbidity, hospital stay, and mortality. Hypoalbuminemia may predict AL, but its early postoperative role is unclear. To assess the association between early postoperative serum albumin and AL in esophageal cancer patients underwent esophagectomy.Materials and methods: In this prospective study, 84 patients with confirmed esophageal carcinoma underwent curative esophagectomy. Serum albumin was measured on postoperative day one. Patients were monitored for AL  and other  complications. Chi-square, t-test, and multivariate logistic regression were used to identify predictors of AL.Results:   Mean  age  was  55.8  ±  9.1  years,  78.6%  were  male.  AL  occurred  in  20.2%  (17/84). Hypoalbuminemia (